Ceramic biomaterials for tissue engineering - Pina, Sandra Cristina Almeida (2018)
Bioceramics, natural and synthetic, are designed to induce a strong bonding to bone and appeared as an alternative to metallic implants. Bioceramic materials currently used for the repair and reconstruction of hard and soft tissues can be categorized according its composition, structure, and properties. These biomaterials are grouped bioinert ceramics as alumina and zirconia, bioactive glasses and glass ceramics and bioresorbable calcium phosphates-based materials. The bioceramics concepts, namely physico-chemical, mechanical and biological properties, and respective applications in diverse fields of tissue engineering are discussed in depth herein. An up-to-date of bioceramics clinical trials is also considered. Based on the stringent requirements for clinical application, prospects for the development of advanced functional bioceramics for tissue engineering are highlighted for the future.